Effect of trace elements Zn, B, Mg and Cu on the growth and sporulation of Pyricularia oryzae, the causal organism of blast disease of rice - Sharma, Renubala; Shukla, Sandeep (Current Botany, 2020)
Blast is one of the most common disease of the Rice crop caused by Pyricularia oryzae. Blast of Rice is a recurrent problem of Rice producing countries declines productivity drastically. Mycelium growth and sporulation of P. oryzae is depend upon many factors i.e. humidity, temperature, availability of nutrients etc. Like other fungi P. oryzae also requires some nutrients in very minute quantity for their physiological and metabolic activities. Regulating these micronutrients or trace elements we can control the growth and spore production in P. oryzae. In this paper, we studied effect of four trace elements i.e. Zinc (Zn), Boron (B), Magnesium (Mg) and Copper (Cu) on growth and sporulation of P. oryzae. Zinc, Boron and Copper are most effective and promote growth and sporulation at 2 ppm (parts per million) concentration when we increased concentration of these elements in the medium, growth and sporulation decreased .On the other hand less growth and sporulation reported in the absence of Magnesium. Minute quantity of Magnesium is required for optimum growth i.e. 2 ppm. after this increasing concentration of Magnesium is not significant.